2020
DOI: 10.1108/jhom-05-2019-0144
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale health system transformation in the United Kingdom

Abstract: PurposeFollowing publication of a new vision for the English National Health Service (NHS) in 2014, known as the NHS Five-Year Forward View, a Vanguard programme was introduced by NHS England charged with the task of designing and delivering a range of new care models (NCMs) aimed at tackling deep-seated problems of a type facing all health systems to a greater or lesser degree. Drawing upon recent theoretical developments on the multilevel nature of context, we explore factors shaping the implementation of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…First, we were not able to account for local contextual factors which might have affected the adoption and implementation of integration processes. Moreover, implemented initiatives were heterogeneous across sites and difficult to describe in detail using interviews and documentary analysis [15,19,[32][33][34][35][36][37]. A recent evidence synthesis of 115 local Vanguard evaluation reports concluded that none of the reports offered "explanations and/or nuanced insights into the Vanguard operation" [38], making crossinitiatives comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we were not able to account for local contextual factors which might have affected the adoption and implementation of integration processes. Moreover, implemented initiatives were heterogeneous across sites and difficult to describe in detail using interviews and documentary analysis [15,19,[32][33][34][35][36][37]. A recent evidence synthesis of 115 local Vanguard evaluation reports concluded that none of the reports offered "explanations and/or nuanced insights into the Vanguard operation" [38], making crossinitiatives comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, the Pioneer or Vanguard programmes have been studied separately [15,19,[32][33][34][35][36][37][38], but never in combination. However, a number of Pioneers subsequently applied to become Vanguards, and thus the two programmes overlapped in time and partially in place.…”
Section: Comparing the Impact Of The Pioneer And Vanguard Programmesmentioning
confidence: 99%
“…The MSC field to date has focused on examples of planned system changes, such as centralising service provision 1,29,30 , integrating different forms of public service 31 , and introducing new technologies into health systems 32 . The case study of changes to elective surgery provision during the pandemic enables investigation of the enablers and consequences of unanticipated, rapid change.…”
Section: Reorganisation Of Elective Surgery As Major Systems Changementioning
confidence: 99%
“…The role of context is well established in implementation science and in recent years attention has been paid to understanding the relationship between context and implementation in mediating change processes in healthcare organisations ( Damschroder et al , 2009 ; Pfadenhauer et al , 2015 , 2016 ; Dopson and Fitzgerald, 2005 ; Kaplan et al , 2010 ; Aarons et al , 2011 ; Bate, 2014 ; Robert and Fulop, 2014 ; Squires et al , 2015 ; May et al , 2016 ; Maniatopoulos et al , 2020 ). This paper identifies and characterises elements of contexts that influenced the introduction (or not) of TEP and the nature of the work to manage them.…”
Section: Introductionmentioning
confidence: 99%